Nasopharyngeal carcinoma in Ibadan, Nigeria: a clinicopathologic study (2020)
Introduction: nasopharyngeal carcinoma is relatively common in our environment. It is one of the most difficult malignancies to diagnose at an early stage. The aim of the study was to determine the clinical features, clinical disease stage of nasopharyngeal carcinoma at presentation and at diagnosis as well as the histologic types at the University College Hospital, Ibadan, Nigeria. Methods: this was a ten year retrospective study of all histologically confirmed nasopharyngeal carcinoma between January 2007 to December 2016 using clinical and pathology records and files. Results: there were 73 cases. The male: female ratio was 1.7. The age of patients ranged from 12 to 80 years with a mean age of 39 ± 16 years. The median age at diagnosis was 40 years. The peak age group of occurrence was 40-49 years. The most common symptoms were namely epistaxis in 67.1% of patients at presentation, neck mass/swelling (64.4%) and nasal mass/obstruction (63.0%). Majority (54.8%) of the patients presented late with stage 3 or 4 disease. Most (94.5%) of the tumours were of the non-keratinizing squamous cell carcinoma subtype. The keratinizing and basaloid variants accounted for 4.1% and 1.4% of the tumours respectively. Conclusion: vague, non-specific symptoms make patients present at late stages of the disease, making it almost impossible to attempt cure. The dominant histopathological type is non-keratinizing squamous cell carcinoma and resembles that seen in most parts of Nigeria and endemic areas of the world